Faktor-Faktor yang Mempengaruhi Kinerja Guru SD di kota Blora Selama Pandemi Covid-19 - Ratih Hesty Utami; Rr. Hawik Ervina Indiworo; Anggun Cahyaningrum (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2021)
This study aims to examine the effect of work environment, work motivation, and work discipline on teacher performance. This research was conducted by means of a case study of public elementary school teachers who worked from home during the Covid-19 Pandemic in Blora City. This research uses descriptive methods and quantitative research types. The population of this study were public elementary school teachers who worked from home during the Covid-19 Pandemic in Blora City. The sample studied was 209 respondents. Data collection techniques used observation and questionnaires with a Likert scale as data collection instruments. The results showed that Work environment (X1) has no significant negative effect on teacher performance, work motivation (X2) has a positive and significant effect on teacher performance, and work discipline (X3) has a positive and significant effect on teacher performance. Simultaneously the work environment, work motivation, and work discipline have a significant influence on teacher performance with a contribution of R2 of 57.1% while the remaining 42.9% is explained by other causes outside the model.